Exploring customer acceptance of artificial intelligence in Vietnam’s hotel industry - Hoang , Le Chi; Do, Nhu Luc (Journal of Finance - Marketing Research, 2025)
Artificial Intelligence (AI) is rapidly becoming integral to global industries, including hospitality. This study investigates the antecedents and mediating factors influencing hotel customers’ intention to adopt AI in Vietnam. A conceptual model was developed, integrating Social Influence, Anthropomorphism, and Hedonic Motivation as predictors, with Performance Expectancy, Effort Expectancy, and Emotion as mediators. Data were collected through a structured online questionnaire distributed to hotel service users, yielding 388 valid responses. Structural equation modeling (SEM) was applied to test the measurement and structural models. The findings show that Social Influence and Hedonic Motivation significantly affect both Performance Expectancy and Effort Expectancy, while Anthropomorphism influences only Performance Expectancy. Hedonic Motivation also enhances Emotion. In turn, both Emotion and Performance Expectancy directly and significantly predict customers’ acceptance of AI. Importantly, the results reveal two novel insights: the negative effect of Anthropomorphism on Performance Expectancy, and the strong direct role of Performance Expectancy in shaping AI adoption. These findings highlight unique cultural and contextual factors within Vietnam’s hospitality sector, extending prior research conducted in other countries. Furthermore, a competitive model comparison revealed that Performance Expectancy exerts a strong direct influence on customers’ readiness to adopt AI, underscoring its pivotal role in the acceptance process.